Automotive aeroacoustics: An overview. (August 2017) - Oettle, Nicholas; Sims-Williams, David
Vehicle aeroacoustic performance has a major influence on customer perception and also has importance for safety and comfort. Wind noise performance was once differentiated by the quality of sealing. Today, achieving competitive wind noise performance also depends on minimising aeroacoustic noise sources generated by the vehicle form, and on attenuation in the noise pathway from sources on the exterior to the vehicle interior. The reduction in noise transmission, especially through glazed surfaces, will continue to play an important role in controlling cabin noise, with a particular emphasis on achieving attenuation efficiently in terms of component mass. The human brain is not only sensitive towards the level of steady broadband noise, but distinctive features such as tonality or modulation draw the attention of the vehicle occupant and impact negatively on perception. Complex indices are often required to define good wind noise performance. This includes the consideration of multiple frequency bands and effects of the range of yaw angles experienced on-road. A key to achieving future vehicle refinement is bringing together an understanding of unsteady onset flow conditions, their impact on cabin sound pressure level and modulation and, in turn, the impact of noise level and modulation on psychoacoustic perception.